2016
DOI: 10.1038/aps.2016.56
|View full text |Cite
|
Sign up to set email alerts
|

Hesperidin alleviates rat postoperative ileus through anti-inflammation and stimulation of Ca2+-dependent myosin phosphorylation

Abstract: Oral administration of hesperidin effectively alleviates rat POI through inhibition of inflammatory responses and stimulation of Ca(2+)-dependent MLC phosphorylation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…Studies by ourselves and others showed that intestinal motility disorder is typically accompanied by infiltration of the multiple inflammatory cells not only in the manipulated intestinal segments but also in the distant unmanipulated gastrointestinal segments . And an increase in the expression of several proinflammatory cytokines and chemokines is commonly present in this case . Furthermore, it is well‐known that there is a strong relationship between inflammation and gut barrier (GB) dysfunction.…”
Section: Introductionmentioning
confidence: 96%
“…Studies by ourselves and others showed that intestinal motility disorder is typically accompanied by infiltration of the multiple inflammatory cells not only in the manipulated intestinal segments but also in the distant unmanipulated gastrointestinal segments . And an increase in the expression of several proinflammatory cytokines and chemokines is commonly present in this case . Furthermore, it is well‐known that there is a strong relationship between inflammation and gut barrier (GB) dysfunction.…”
Section: Introductionmentioning
confidence: 96%
“…MLCK protein expression in jejuna of constipated rats was examined using western blot as described previously [ 16 ]. Ardipusilloside-I at doses of 25, 50, 100 mg/kg was gavaged to constipated rats daily respectively as mentioned above.…”
Section: Methodsmentioning
confidence: 99%
“…Those rats that were supplemented with doses of 50 mg/kg, 100 mg/kg, and 200 mg/kg prior to lipopolysaccharide-induced endotoxicity showed an improvement in endothelial status with respect to those that were not treated [ 38 ]. The capacity of hesperidin to down-regulate inflammatory status has been reported to improve rat postoperative ileus in a dose-dependent manner between 5 and 80 mg/kg [ 39 ]. A dose of 160 mg/kg in rats reduced lipid peroxidation and improved the activity of endogenous antioxidant enzymes, palliating effects of rheumatoid arthritis [ 40 ].…”
Section: Natural Extracts and Compounds With Anti-inflammatory Promentioning
confidence: 99%